1987
DOI: 10.2307/1939226
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Competition, and the Structure of Temperate Zone Lizard Communities

Abstract: The roles of climate and competition in relation to the structure of temperate zone lizard communities were investigated. Lizard species richness was positively related to mean January temperature, but negatively related to warm-season precipitation and mean July temperature. Generic groups showed little overlap in morphological factor space but considerable overlap in habitat use. Species that were similar in either morphology or habitat use were dissimilar in the alternative factor space. A canonical correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 75 publications
1
26
0
2
Order By: Relevance
“…Our analysis thus provides evidence that water availability places strong constraints on diversity in the temperate zone (Hawkins et al 2003a). Several studies have suggested that available water is associated with lizard richness and other animal species (Scheibe 1987;Rahbek and Graves 2001;Hawkins et al 2003b;Costa et al 2007). It appears contradictory to the physiological independence of most lizard species from aquatic or moist situations.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our analysis thus provides evidence that water availability places strong constraints on diversity in the temperate zone (Hawkins et al 2003a). Several studies have suggested that available water is associated with lizard richness and other animal species (Scheibe 1987;Rahbek and Graves 2001;Hawkins et al 2003b;Costa et al 2007). It appears contradictory to the physiological independence of most lizard species from aquatic or moist situations.…”
Section: Discussionsupporting
confidence: 57%
“…Several previous studies attempted to test these competing hypotheses at different spatial scales using lizard species as model systems. Temperature (Pianka 1967;Scheibe 1987;Fu et al 2007;Powney et al 2010), precipitation (Scheibe 1987) and the number of hours of sunshine (Schall and Pianka1978) have been correlated with lizard species richness, whereas topographic heterogeneity (Owen 1989), actual evapotranspiration (AET) (Powney et al 2010) and potential evapotranspiration (PET) (Fu et al 2007) have been suggested to explain lizard species richness. The driving factors of these results may vary across geographical scale (Powney et al 2010), but increasing studies on other taxa suggest that a series of competing hypotheses or predictors may play different roles to explain species richness variation over broad spatial scales (Costa et al 2007;Gaston 2000;Kerr et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that factors such as interespecific competition (SCHOENER 1977, SALZBURG 1984, NÚÑEZ et al 1989), predation (GIBBONS & LILLYWHITE 1981, size and morphology of the lizard (MARCELLINI & MACKEY 1970, ASPLUND 1974, SCHEIBE 1987, and seasonal and ontogenetic variations (PAULISSEN 1987) may influence microhabitat use. ADOLPH (1990) concluded that microhabitat use by a particular species of lizard reflects an overlap between thermally appropriate conditions for the species' average size and behavioral preferences.…”
mentioning
confidence: 99%
“…The higher the energy input, the more emergent properties would be produced within a system. This quality has been proved by species richness distribution of birds Root, 1988;Turner, 1988), Lizard (Scheibe, 1987), vascular plants (Mittelbach et al, 2001), benthic marine algae (Kerswell, 2006), etc. So energy is generally positively related to ecosystem creativity.…”
mentioning
confidence: 94%